Effect of Rare Earth Oxides (Y2O3, Nd2O3) on Oxidation Kinetics of Al-Li base alloy - Abbass, Muna K. (Nahrain University College of Engineering Journal, 2007)
The oxidation of Al-Li base alloy containing small amounts of rare earth (RE) oxides such as Y2O3 and d2O3 particles has been studied at temperatures between 300°Cand 550°C. The lithium is selectively oxidized in Al-Li alloys and the parabolic rate constants for the growth of the resulting oxides layer Li2O, LiAl5O8, Li2CO3 and Li5AlO4 are about an order of magnitude higher than those for growth of oxides on alloy (Al-Li) with RE oxides. Alloys used in this study were prepared by melting and casting in a permanent steel mould under controlled atmosphere. It was found that 0.2%Y2O3 containing alloys possess the lowest oxidation rate and show great improvements in oxidation resistance compared to the base alloy. Oxides found on base alloy are subjected to cracking and spalling during thermal shock at high temperature i.e. 500°Cand 550°C. Identification of oxidation kinetics was carried out by using weight gain measurements while scanning electron microscopy (SEM) and x-ray diffraction analysis were used for microstructural morphologies and phase identification of the oxide scales. The weight gain measurement results suggest that the oxidation kinetic of all studied alloys follows the parabolic law in most experimental tests under the different temperatures except at 300°C oxidation kinetic follows almost a logarithmic rate law .